Of girls and horses [videorecording (DVD)] - Treut, Monika; Schmitz-Chuh, Céci, 1991-; Wilms, Alissa, 1995-; Karun, Vanida, 1979- (Wolfe Video, LLC, 2015)
A rebellious teen is sent away to a horse ranch by her mother. She's determined not to change one iota, but the horses--and the resident riding instructor, Nina--become increasingly dear to her.